Zinc Deficiency may Synergies the Taste Impairment of Terbinafine: A Case Report (International Journal of Scientific Research in Science and Technology, 2024)
Terbinafine, an oral antifungal belonging to the allylamine class, was introduced in 1991 and is now widely used for both topical and systemic treatment of fungal infections, including tinea corporis. An eighteen-year-old male patient presented with a skin infection diagnosed as tinea corporis, with a known history of acrodermatitis enteropathica, an inherited zinc deficiency disorder. Zinc is an essential component for normal taste perception. It is initiated as antifungal therapy by administering 250 mg of oral terbinafine (Sebifin) daily. During a follow-up appointment two weeks into the treatment, the patient reported altered taste sensations, including a diminished ability to taste bitter and sour flavours and a partial loss of sweet and salty taste. The taste disorder began five days after starting the medication. Suspecting terbinafine-induced taste impairment, the drug was immediately discontinued. The patient's taste function fully recovered five days after discontinuation, indicating the reversibility of this adverse effect. This case highlights the importance of monitoring for potential side effects during antifungal therapy, particularly in patients with underlying conditions such as acrodermatitis enteropathica (zinc deficiency).
Keywords: Terbinafine; Zinc deficiency; Tinea corporis; Taste impairment